Ações afirmativas no sistema educacional: trajetórias de jovens negras da Universidade de Brasília - (:unkn) unknown (Ministério Público do Estado da Bahia, 2008)
This article presents the experiences of black female students admitted by the University of Brasília through the affirmative action programme. They attend courses in Engineering and Social Sciences and have experienced different school socialization processes. By choosing students of different academic courses and school backgrounds we tried to analyse their experiences with racism and prejudice and also the strategies to overcome these situations. A second focus of our analyses lies on the experiences of black female students and their attitude toward affirmative action in public universities of Brazil. We agreed that it is not sufficient to say that this policies are fair because they are in accordance to the imperative of social justice, if the results are not evident. The establishment of systems of quotas is not the only way of recognition and redistribution, but it reflects the necessity of an adjustment of the university system to the political and social requirements of the Brazilian society and its people.
Afirmative action in the educational system: trajectories of young black women at the university of Brasília
Keywords: Ação afirmativa; Preconceito racial; Negros - Educação; Universidade - Discriminação; Gênero; Sistema de cotas; CNPQ::CIENCIAS SOCIAIS APLICADAS::DIREITO